Hate in the Time of COVID-19: Racial Crimes against East Asians - Joel Carr; Jonathan James; Joanna Clifton-Sprigg; Suncica Vujic (Institute of Labor Economics (IZA), 2022)
We provide evidence of the impact of the COVID-19 pandemic on racial hate crime in England and Wales. Using various data sources, including unique data collected through Freedom of Information (FOI) requests from UK police forces, a difference-in-difference and event study approaches, we find that racial hate crime against East Asians increased by 70-100%, beginning in early February and persisted until November 2020. This increase was greatest in the weeks leading up to the first national lockdown in the UK. The shock was then lower during lockdown, before increasing again in the summer 2020. We present evidence that hate crime increased as COVID-19 cases in China increased and following announcements from the government signalling that China or Chinese individuals posed a public health risk to the UK. This indicates that protectionism played an important role in the observed hate crime spike. The hate crime shock was also positively correlated with the salience of the national lockdown and government policies restricting certain freedoms. The effect was driven largely by changes in London. This suggests that retaliation for lockdown contributed to the rise in hate crime.
Keywords: J15; C23; D63; 330; COVID-19; hate crime; xenophobia; difference-in-differences; event study